Effect of olive oil on the preparation of nanoemulsions and its effect on aroma release - Ren, Jing-Nan (J Food Sci Technol, 2018)
The present study focused on the effect of olive oil on Ostwald ripening of flavor nanoemulsions. The release of the aroma compounds from the nanoemulsion system was also investigated. The results showed that the droplets size of the nanoemulsions decreased sharply first and then kept stable with the increase of Tween 80. The optimum surfactant/cosurfactant (Km) ratio was determined at 7:1. The average particle size of nanoemulsion was 39.22 nm. The polydispersity index (PDI) was 0.242 nm, and the particle size distribution was in the range of 20–150 nm at the optimum Km. The stability of the nanoemulsions was improved after the addition of olive oil, and it increased noticeably with the increase of olive oil. The addition of olive oil could help to stabilize the emulsions and hamper Ostwald ripening. All the 11 aroma compounds in the nanoemulsions were detected after 24-h storage. While only 5 aroma compounds were found after 48-h storage, and α-pinene and β-myrcene were the only two aroma compounds detected after 72-h storage with low contents of 1.41 and 0.5 mg/L. The addition of olive oil inhibited the release of the aroma compounds from the nanoemulsion system. The released ethyl acetate was reduced by 48% after the addition of 10% olive oil. Significant decrease on the release of α-pinene and nonanal was observed after the addition of 3% olive oil. And the decrease was also observed on the release of β-myrcene, D-limonene, α-terpineol, decanal and eugenol when the olive oil content was ≥ 5%. However, benzyl alcohol, β-ionone and 1-octanol showed no significant changes with the increase of olive oil. This indicated that the addition of olive oil could provide greater retention of the aroma compounds in the nanoemulsions.